GRANTING THE RIGHT OF USE ON FREEHOLD LAND TO FOREIGN CITIZENS IN BADUNG REGENCY - Sumiati, Ni Kadek; Suwitra, I Made; Renaya, Nengah (YURIS: Journal of Court and Justice, 2024)
As a solution to address the interest of foreign citizens to own houses and land in Indonesia, the Government regulates this in Article 41 and Article 42 of Law No. 5/1960 (UUPA) as well as Government Regulation No. 18/2021 on Management Rights, Land Rights, Flat Units, and Land Registration. However, obtaining such rights requires time, significant costs, and the fulfillment of certain conditions. Often, foreigners are reluctant to engage in complicated and time-consuming processes, preferring the easy, cheap and fast way. In addition, there is a practice of land tenure by foreigners which in reality is considered a form of legal smuggling. Hence, this research aims to identify and analyze the granting of right of use on freehold land to foreign citizens in Badung Regency, as well as to identify and analyze the effectiveness of laws and regulations in granting right of use on freehold land to foreign citizens in Badung Regency. This research is juridical empirical, with primary data obtained through direct interviews with respondents and informants in the field, while secondary data is obtained through library research on primary, secondary, and tertiary legal materials. The research findings revealed that the implementation of the provisions on the granting of the right of use on freehold land for foreign citizens in Badung Regency has been effective, as the data suggest that foreign citizens in Badung Regency have obtained land rights in accordance with the provisions of the law.